Tortoises and hares: the race to shared services across Australian state and territory jurisdictions - Dollery, Brian; Grant, Bligh (2010)
All tiers of government in Australia have recently aimed at enhancing service provision, with shared service platforms a recent innovation. to date there has been no scholarly inquiry into comparative shared service performance at the Australian state level. This article evaluates the experience of different state jurisdictions in adopting shared service platforms within "Whole of Government" approaches to public sector reform. It demonstrates that those jurisdictions most eager to embrace shared services have created organizations susceptible to particular adverse outcomes and that, far from implementing shared services programs, they may have installed monopoly-provider conditions for a range of back-office functions. - Reproduced.
Keywords: State governments - Australia; State governments